Managerial Competencies of Officers and Financial Performance of Selected Agricultural Micro Cooperatives in The Province of Isabela (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Cooperatives in the Philippines to this present day already existed for more than a century since its legislated amalgamation to the socio-economic governance of the country in 1916. Throughout those more than 100 years, it has its successes and failures of which management is a crucial factor. This study investigated further the managerial competency of cooperative officers and financial performance of selected agricultural micro cooperatives in the province of Isabela. Data were gathered from all the selected 37 only compliant cooperative represented by 185 officers as respondents. The study mainly sought to answer if there is relationship between cooperative officers and managerial performance, cooperatives profile and financial performance and core managerial competency and cooperative financial performance of cooperatives. The study revealed that majority of the selected agricultural micro cooperatives served as respondents of this study had a fair financial performance rating, that only educational attainment variable had significant correlation with managerial competency. The cooperative cooperatives profile and financial performance was found of having no significant relationship and there is no significant correlation of the managerial competencies and cooperative financial performance. Based on the findings of the study a proposed action plan was formulated for the agricultural micro cooperatives. Notably recommended that the Cooperative Development Authority and other government and private entities and stakeholders in the administration, supervision and supporting the cooperatives may conduct necessary, relevant and timely trainings or continuing education and other development initiatives and actions to assist more the agricultural micro cooperative to have a reliable and accurate Management Information System and data analytics useful in decision-making specially to achieve a sound financial performance.